Comparison of highly conductive natural and synthetic graphites for electrodes in perovskite solar cells. (30th June 2021) - Bogachuk, Dmitry; Tsuji, Ryuki; Martineau, David; Narbey, Stephanie; Herterich, Jan P.; Wagner, Lukas; Suginuma, Kumiko; Ito, Seigo; Hinsch, Andreas
Abstract: In this work we compare seven different types of natural and synthetic graphite particles and examine how their integration into the cathode of carbon-based perovskite solar cells (C–PSCs) is influencing their opto-electronic properties. By combining x-ray diffraction, Raman spectroscopy and 4-point probe measurements we show that the differences in graphite crystallinity significantly affect the sheet resistance of the carbon-based cathode. The most conductive carbon-based film with an exceptional sheet resistance of 4 Ω/sq. have been produced from scaly graphite with the crystallite dimensions of La = 60.6 nm and Lc = 28.6 nm. Electrochemical Impedance Spectroscopy further revealed that charge transfer resistance at the perovskite/carbon contact differ for each graphite type. Overall, the pyrolytic graphite was found to be the best compromise between high conductivity and low charge transfer resistance leading to least series resistance losses and a fill factor (FF) above 74% (in perovskite solar cells with area of 0.64 cm 2 ). However, an overall efficient hole extraction and lower non-radiative charge recombination in C–PSCs with scaly graphite resulted in the highest average power conversion efficiency and a champion device reaching 14.63%. All the C–PSCs show exceptional moisture stability for 5, 000 h under ambient condition, with a PCE decrease of less than 3%. Graphical abstract: Image 1